A New Framework for the Regeneration Process of Mediterranean Historic City Centres - Tanrikul, Ali; Hoskara, Sebnem (Mdpi, 2019)
For thousands of years, cities have evolved with changing needs. Cities are like living organisms, which are exposed to transformations as a result of changing needs and requirements. City centres are one of the attractive, essential, and vital parts of the city that are also affected by these changes. Specifically, historic city centres, which refer to the origins of the city, will be discussed within this context. Urban design aims to shape our cities with better quality and provide better places for everyday life. In addition, urban regeneration can be utilized as generic public policy for solving problems and providing physical improvements for these cities. Although the problems that emerge in each city are similar, sometimes they change circumstantially. As a result, the planning, implementation, and management of urban regeneration projects as well as their sustainability can produce serious complications. This article focuses on the process of urban regeneration, historic city centres, and the Mediterranean region and aims to develop an applicable regeneration framework for historic city centres limited to the Mediterranean region. First, the main problems of these cities are described. Next, characteristics of historic city centres and associated problems of the Mediterranean region are explained. Subsequently, the concept of urban regeneration is clarified, and the processes involved are discussed. Finally, an applicable urban regeneration framework for historic Mediterranean city centres, developed by the authors, is explained with the goal to reduce social segregation while incorporating the contributions of views from both local inhabitants and stakeholders in the process. The methodology of the overall research presented in this article is mainly based on a critical review of primary and secondary documents from the literature through a comparative and exploratory approach.
Keywords: sustainability; urban regeneration; regeneration process; framework; historic city centre; Mediterranean